Advancing frontiers: Kulliyyah of Engineering Research, Innovation and Commercialisation Exhibition (KERICE 2025) - Mat Harttar @ Mohd Hatta, Maziati Akmal (Kulliyyah of Engineering (KOE), IIUM, 2025)
Advancing Frontiers: Kulliyyah of Engineering Research, Innovation & Commercialisation Exhibition (KERICE 2025) brings together the diverse research outputs, innovations, and scholarly ideas from the Kulliyyah of Engineering, International Islamic University Malaysia. With the theme “Sustainable Academia–IndustryCommunity Collaboration for Humanity”, KERICE 2025 provides a platform to promote quality research, foster exchange of ideas, and highlight the Kulliyyah’s research excellence. It also serves as a bridge between academia and industry, strengthening collaborations that translate knowledge into impactful solutions. Since its establishment in 1994, the Kulliyyah of Engineering has aspired to be “A Global Centre of Innovative Engineering Education and Research with Values and Professional Ethics.” This publication reflects that vision and celebrates the spirit of innovation that drives engineering towards advancing frontiers for humanity.